Pengaruh Entrepreneur Leadership, Innovation, Engagement, dan Self Efficacy Terhadap Employee Performance PT Waroeng Batok Industry - Suyoto; Hengky Widhiandono; Sony Yuliansyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
PT Waroeng Batok Industry (WBI), a company engaged in the manufacture of wooden boards located in West Cilacap City, Central Java. The purpose of this study was to analyze the influence of entrepreneurial leadership, innovation, engagement and self-efficacy on employee performance of PT. Waroeng Batok Industry. This study used a questionnaire method as data collection. The sample selected using random sampling. Based on the criteria obtained 102 respondents. This study used the SPSS test tool, with the research methods used were descriptive statistical analysis test, classical assumption test, multiple regression analysis, coefficient of determination, f test, and t test. The results showed that entrepreneurial leadership, engagement and self-efficacy had a positive effect on employee performance of PT. Waroeng Batok Industry. While Innovation did not affect employee performance of PT. Waroeng Batok Industry.